A sequencing-based method for quantifying gene-deletion mutants of bacteria in the intracellular environment - Fei, Xiao; Yuan, Zengzhi; Wellner, Sandra Marina; Ma, Yibing; Olsen, John Elmerdahl (Frontiers in Microbiology, 2025)
Advancements in next-generation sequencing (NGS) have significantly accelerated the development of innovative methodologies in microbiological research. In this study, we present a novel method to quantify the net survival of gene-deletion mutants within the intracellular environment. Based on standardized Illumina short-read sequencing of genomic DNA, the method eliminates the need for specific selective markers on each deletion mutant. For validation, the method was shown to accurately quantify mutants in spiked pools of mixed mutants, showing no statistically significant differences compared to the expected values based on CFU determination (p > 0.05). Further, the method was used to quantify mutants of S. Gallinarum in macrophages. Six mutants and one control strain were mixed in a pool and allowed to infect HD11 cells for 2 h. The results align with prior research results, providing evidence of the feasibility of mixed mutant infections in functional gene identification. Notably, the simplicity and standardization of the method, rooted in standard whole-genome sequencing protocols, make it easily implementable across various laboratories.